A hospital based case control study to explore the association between Bruxism and Cardiovascular diseases in Kangra region of Himachal Pradesh - Bhatia, Ragini; H., Divya Nair; Bhatnagar, Mukul Kumar; Sood, Saloni; Kumar, Praveen; Chaudhary, Rajesh (International Journal Of Community Medicine And Public Health, 2021)
Background: Cardiovascular diseases (CVDs) have a huge social and economic impact all over the world. Therefore research needs to analyse emerging risk factors for CVDs. Bruxism is a health problem that has low prevalence in the community but may be associated with CVDs. It leads to poor oral health and significantly impacts the quality of life. Studies showing association of CVDs and Bruxism are sparse and, none in Indian context. Methods: This study was conducted in two hospitals of Kangra region of Himachal Pradesh between the months of April 2020 to June 2020. Due to rising infection rates of COVID-19 cases, 160 patients were enrolled in the study and divided into two groups. 80 patients with a positive history for CVD were included as cases while another 80 patients without any known history for CVD were included in the control group. Self-reporting questionnaire and tooth wear index (TWI) were used as research instruments. Results: An unadjusted odd’s ratio of 2.43 (95% CI, 1.28-4.68) and p value of 0.0069, was found when only self-reported bruxism was taken into account. But when self-reporting of bruxism was combined with TWI, an unadjusted odd’s ratio (logit OR) of 3.16 (95% CI, 1.66-6.21) and p value of 0.000529 was found, explaining that the odds of having CVD are 3.16 times higher in patients with bruxism than in those without bruxism. Conclusions: Bruxism is significantly associated with cardiovascular diseases. More studies, with larger sample size are required to firmly establish the causative relationship between bruxism and CVDs.